Biofunctional Understanding and Conceptual Control: Searching for Systematic Consensus in Systemic Cohesion - Iran-Nejad, Asghar; Bordbar, Fareed (Frontiers in Psychology, 2017)
For first generation scientists after the cognitive revolution, knowers were put in active control over all (stages of) information processing. Then, following a decade of transition shaped by intense controversy, embodied cognition emerged and suggested sources of control other than those implied by metaphysical information processing. With a thematic focus on embodiment science and an eye towards systematic consensus in systemic cohesion, the present study explores the role of biofunctional and conceptual control processes in the wholetheme spiral of biofunctional understanding (see Iran-Nejad & Irannejad, 2017b, Figure 1). According to this spiral, each of the two kinds of understanding has its own unique set of knower control processes. For conceptual understanding (CU), knowers have deliberate attention-allocation control over their first-person “knowthat” and “knowhow” content combined as mutually coherent corequisites. For biofunctional understanding (BU), knowers have attention-allocation control only over their knowthat content but knowhow control content is ordinarily conspicuously absent. To test the hypothesis of differences in the manner of control between CU and BU, participants in two experiments read identical-format statements for internal consistency, as response time was recorded. The results of Experiment 1 supported the hypothesis of differences in the manner of control between the two types of control processes; and Experiment 2 confirmed the results of Experiment 1. These findings are discussed in terms of the predicted differences between BU and CU control processes, their role in regulating the physically-unobservable flow of systemic cohesion in the wholetheme spiral, and a proposal for systematic consensus in systemic cohesion to fill the second slot for a guiding principle in biofunctional embodiment science next to physical science’s first guiding principle of systematic observation.